Improved physical performance in obesity-resistant rats compared to obesity-prone rats: Effects of different diets and metabolic analysis. - Daniel Sesana da Silva; Matheus Corteletti Dos Santos; Lucas Furtado Domingos; Jóctan Pimentel Cordeiro; Kiany Miranda; Maria Gabriela Siqueira Tavares; Késsia Cristina Carvalho Santos; Ana Paula Lima-Leopoldo; André Soares Leopoldo (PLoS ONE)
Animal models, such as high-fat diet-induced obese (DIO) rats, have been used to understand its pathophysiology. These models reveal differences between obesity-prone (OP) and obesity-resistant (OR) phenotypes. Thus, OR exhibit lower body mass gain and higher levels of physical activity, suggesting a more efficient energy metabolism. This study evaluated the metabolic adaptations and physical performance of OP and OR rats. Wistar rats (30 days old) were subjected to 23-week obesity exposure protocols. Initially, rats were randomized into two groups: a) SD: fed a standard diet (n = 39) and b) HFD: fed a high-fat diet (n = 39). Subsequently, animals were characterized as OP and OR on their respective diets: SD-OR (n = 13); SD-OP (n = 13); HFD-OP (n = 13); HFD-OR (n = 13). Nutritional, metabolic, and adiposity parameters were analyzed. Basal metabolism assessment was performed using indirect calorimetry. Physical performance and aerobic capacity were determined through treadmill exercise tests with gas analyzers for maximal oxygen consumption (VO2). OR animals had lower body mass compared to OP animals, despite consuming the same caloric intake under both diets. HFD-OP rats gained 30.5% more weight than HFD-OR rats, while SD-OP rats gained 19.5% more than SD-OR rats. SD-OR rats gained 20.5% more weight than HFD-OR. No significant differences in adiposity indices were observed among groups. HFD-OR rats showed 15.6% higher VO₂max than HFD-OP rats; SD-OR rats had 12.8% higher VO₂max and 20.3% longer time to exhaustion compared to SD-OP rats. Indirect calorimetry revealed higher energy expenditure in OR animals during the dark cycle. OP animals exhibited elevated insulin and HOMA-IR levels, while OR animals had higher leptin and glucagon levels. In conclusion, OR rats showed improved physical performance and aerobic capacity compared to OP rats, even on a high-fat diet, suggesting that OR rats have adaptive mechanisms that enhance energy metabolism and endurance.